The influence of the pectin structure on the properties of hydrogel dressings doped with octenidine-containing antiseptic - Fiedot, Marta; Junka, Adam; Brożyna, Malwina; Cybulska, Justyna; Zdunek, Artur; Kockova, Olga; Lis, Krzysztof; Chomiak, Katarzyna; Czajkowski, Maciej; Jędrzejewski, Roman; Szustakiewicz, Konrad; Cybińska, Joanna; et al. (Carbohydrate polymers, 2024)
This article presents a method for producing hydrogel dressings using high methylated pectin from apples or citrus, doped with the antiseptic agent, octenidine dihydrochloride. Octenidine was incorporated in-situ during the polymer crosslinking. The pectins were characterized by their varying molecular weight characteristics, monosaccharide composition, and degree of esterification (DE). The study assessed the feasibility of producing biologically active hydrogels with pectin and delved into how the polymer's characteristics affect the properties of the resulting dressings. The structure evaluation of hydrogel materials showed interactions between individual components of the system and their dependence on the type of used pectin. Both the antimicrobial properties and cytotoxicity of the dressings were evaluated. The results suggest that the primary determinants of the functional attributes of the hydrogels are the molecular weight characteristics and the DE of the pectin. As these values rise, there is an increase in polymer-polymer interactions, overshadowing polymer-additive interactions. This intensification strengthens the mechanical and thermal stability of the hydrogels and enhances the release of active components into the surrounding environment. Biological evaluations demonstrated the ability of octenidine to be released from the dressings and effectively inhibit the growth of microbial pathogens.
Keywords: Hydrogel dressing; Anti-Infective Agents, Local; Molecular Weight; Bandages; In-situ doping; molekulová hmotnost; pektiny; hydrogely; Pyridines; pyridiny; Octenidine; Microbial Sensitivity Tests; antiinfekční látky lokální; Staphylococcus aureus; Pectins; Imines; High methylated pectin; Polymer structure; zvířata; Malus; Hydrogels; Citrus; Humans; iminy; mikrobiální testy citlivosti; obvazy; lidé; Animals